THWARTING WORMHOLE ATTACK IN RPL BASED IoT NETWORKS - C.Kayalvizhi, P.S.Nandhini, Dr.S.Malliga, B.Madhumitha, P.Elango (International Journal of Advanced Science and Technology, 2020)
Routing protocol for Low Power and Lossy Network (RPL) is a resource constrained network protocol. Low Power Lossy Network (LLN) consists of number of constrained nodes and links. RPL (RFC 6550) is one among the LLN standards. It allows the transmitter of the packet to mention the route for packet transmission. So, the destination reachability should be verified before transmission. It is verified by transmitting the control packets of RPL.The characteristics of RPL based Internet of Things(IoT) are communication of devices over the constrained networks, unreliable Internet connectivity, lossy nature of communication link and the heterogeneous nature of IoT devices. Therefore, they are prone to various attacks. Thus, providing security for RPL based IoT is a big challenge. In the Wormhole attack, the attackers trap the packet from one point of location and transmit them to other distant located nodes via creating a tunnel between the nodes. The attackers are identified by calculating the RSSI values. If attack is detected, the proposed method prevents the packet from reaching the attacker. The design of the proposed system is helpful in providing security to the IoT network.The proposed method is beneficial in the resources constrained environment also.